2016
DOI: 10.1007/s40093-016-0126-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of textile sludge on the growth of red amaranth (Amaranthus gangeticus)

Abstract: Purpose In Bangladesh, the sludge of textile effluent treatment plant has been considered as a potential environmental threat due to its huge volume and chemical content. Thus, the present study was carried out to assess the reuse possibility/potentiality of textile sludge in agricultural applications. Method Textile sludge was applied at different loading ratios (0-100 % sludge) with soil for the pot cultivation of red amaranth (Amaranthus gangeticus); subsequently, chemical analyses were carried out on the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Application of organic waste is recommended due to the potentials of organic waste to increase soil pH and nutrients and thus reduce heavy mineral fertilizer application to agricultural soils (Unagwu et al 2013;Unagwu 2014Unagwu , 2019Nessa et al 2016;Joardar and Rahman 2018). Under intensive agriculture, continuous chemical fertilizer application is reported to increase soil acidity which creates nutrient imbalance in the soil (Ojenyi 2000) and consequently reduces crop yield.…”
Section: Introductionmentioning
confidence: 99%
“…Application of organic waste is recommended due to the potentials of organic waste to increase soil pH and nutrients and thus reduce heavy mineral fertilizer application to agricultural soils (Unagwu et al 2013;Unagwu 2014Unagwu , 2019Nessa et al 2016;Joardar and Rahman 2018). Under intensive agriculture, continuous chemical fertilizer application is reported to increase soil acidity which creates nutrient imbalance in the soil (Ojenyi 2000) and consequently reduces crop yield.…”
Section: Introductionmentioning
confidence: 99%
“…When sludge is dumped into landfills or burned in incinerators, the produced leachate, gases, and ash contents release secondary pollutants into the environment [26]. With a production rate of 1.14 kg per m 3 of wastewater produced in 2012, they produced 36.39 Mt of sludge [27,28]. According to the "Bangladesh Standards and Guidelines for Sludge Management" [29] sludge is divided into three categories: Category A, which comprises municipal and equivalent sludge; Category B, which includes sludge from industries such as the CETP (Central Effluent Treatment Plant); Category C, which contains sludge from industries that handle hazardous waste, including the CETP.…”
Section: Introductionmentioning
confidence: 99%
“…Rahman et al [31] reported the usage of sludge as a partial replacement of sand in mortar and concrete that has exhibited compressive strength values of 20.0 and 12.0 MPa, respectively, and commented that sludge can be a potential agent for building materials. Nessa et al [28] conducted a study to identify the reuse potential of textile sludge in agricultural activities. Nevertheless, none of the research addressed sludge management inside the plant compound and the challenges businesses confront in doing so.…”
mentioning
confidence: 99%
“…Nonetheless, there may be positive or negative effects depending on the dose and concentration of heavy metals and nutrients in the sludge (Santos et al 2011;de Andrade et al 2016). Some studies have proved that the sludge can stimulate microbial communities in edaphic environments (Nakatani et al 2012;Silva et al 2014), and plants (Silva et al 2010;Patel et al 2015;Nessa et al 2016) due to the pH regulation and the increment of nutrients and organic carbon. Moreover, the amendment of wastes with high concentration of heavy metals may cause toxicological damage to soil systems (Celary and Sobik-Szołtysek 2014;Oliveira et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Disposal of organic waste on soil may be recommended due to the potential use for increasing the soil pH and nutrients. These provide a reduction in the application of mineral and commercial inputs, reducing costs of agricultural cultures and improving soil quality, once organic waste can act as soil conditioner (Gianello et al 2011;Bose and Bhattacharyya 2012;Nessa et al 2016;Joardar and Rahman 2018). Therefore, the amendment of soil with industrial landfill sludge (ILS) may be seen as an environmental alternative to the final disposal of those wastes.…”
Section: Introductionmentioning
confidence: 99%